PENGABAIAN ORANG TUA DALAM DUNIA DIGITAL ANAK: IMPLIKASI TERHADAP HAK ASUH MENURUT HUKUM ISLAM - Sapri Ali; Nalita Hajar Aswad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Digitalization brings changes in childcare, especially media and technology sources, as more and more parents allow their children to be stimulated by the presence of a shared position with the adopted position of children at various moral, social, and spiritual levels. This is a form of legal neglect of the executive parent and in the perspective of Islamic law is defined in terms of the mandate of care (ḥaḍānah). The purpose of this study is to express and detail the same problem, as well as convey information and scientific issues and opinions regarding the position of the digital world on children in this study using various library research methods and theological-normative, psychological, and sociological approaches and the rules of the Qur'an, hadith, classical books (yellow books) and Law No. 35 of 2014 concerning Child Protection, issued. This is assessed internally and externally. Digital consumption without parental supervision can influence the emergence of deviant behavior leading to vulgarity, online game addiction and disrespect towards parents. From an Islamic perspective, parents not only